(untitled) (Reflection and Critique Law Magazine, 2026)
This study investigates the factual and institutional barriers limiting access to justice and citizenship for stateless persons in Brazil under the framework of the Migration Law (Law No. 13,445/2017). The general objective is to analyze the bureaucratic and linguistic obstacles that perpetuate the "legal invisibility" of these individuals in the national context. Specifically, it intends to contrast the eugenic policies of the 20th century with the current humanitarian paradigm, identifying failures in strategic cooperation between the Ministry of Foreign Affairs (Itamaraty) and the Federal Public Defender’s Office (DPU). The research is justified by the extreme vulnerability of stateless persons, individuals deprived of sovereign ties and hindered by slow processes such as diploma revalidation. A qualitative methodology was used with bibliographic and documentary analysis. It concludes that the effectiveness of legal protection is stifled by a lack of institutional training and the lack of preparation of bodies such as the Federal Police. As final considerations, the study proposes the urgent regulation of Article 120 of the Migration Law to create a coordinated national policy, the strengthening of the DPU, and the inclusion of a specific constitutional protection clause for stateless persons, aiming to ensure substantive equality and the eradication of the phenomenon in Brazilian territory